Incidentally Detected Malignancies in Lung Explants. (December 2022) - Razia, Deepika; Arjuna, Ashwini; Trahan, Amy; Hahn, Mary F.; Abdelrazek, Hesham; Omar, Ashraf; Tokman, Sofya; Hashimi, Abdul Samad; Huang, Jasmine; Smith, Michael A.; Bremner, Ross M.; Walia, Rajat
Introduction: Incidentally detected malignancies in lung explants portend risk of early cancer recurrence and metastases with posttransplant immunosuppression. We present a series of lung transplant recipients with previously unverified malignancies in native lung explants.Design: We reviewed the histopathology, radiographic imaging, and management of lung explant malignancies at our institution over 10 years (2011-2020). Endpoints were survival and allograft rejection.Results: An explant malignancy was found in 1.3% (11/855) of lung transplant recipients (6 [55%] men; median age 68 years; 6 [55%] ex-smokers [median pack-years, 25]). Nine (82%) were adenocarcinoma, 1 (9%) was squamous cell carcinoma (SCC), and 1 (9%) was follicular lymphoma. Three patients (27%) had multifocal involvement (≥3 lobes), 4 (36%) had nodal involvement, and the median (range) tumor size was 2.7 (0.4-19) cm. The median interval between last imaging and transplant was 58 (29-144) days. Mycophenolate mofetil was discontinued or reduced in all; everolimus was used in 2 patients, and cisplatin-pemetrexed chemotherapy was used in 2 patients. The prevalence of acute cellular rejection and chronic rejection was 27% and 9%, respectively. Lung recipients with cancer had significantly lower survival than those without (36.4% vs 67.3%, p = 0.002); median survival was 27 (17, 65) months in 4 recipients who were alive and cancer-free at the end of the study period.Conclusions: Unidentified malignancies, commonly adenocarcinoma, can be detected in explanted native lungs. Pneumonectomy may be curative in SCC, lymphoproliferative disorders, and stage I adenocarcinoma. Modulating immunosuppression to prevent allograft rejection and tumor proliferation is warranted.